The effect of warm-ups incorporating different volumes of dynamic stretching on 10- and 20-m sprint performance in highly trained male athletes - Turki, O.; Chaouachi, A.; Behm, D. G.; Chtara, H.; Chtara, M.; Bishop, D.; Chammari, K.; Amri, M. (The Journal of Strength and Conditioning Research, 2012)
Recently, athletes have transitioned from traditional static stretching during warm-ups to incorporating dynamic stretching routines. However, the optimal volume of dynamic drills is yet to be identified. The aim of this repeated-measures study was to examine varying volumes (1, 2, and 3 sets) of active dynamic stretching (ADS) in a warm-up on 10- and 20-m sprint performance. With a within-subject design, 16 highly trained male participants (age: 20.9 ± 1.3 years; height: 179.7 ± 5.7 cm; body mass: 72.7 ± 7.9 kg; % body fat: 10.9 ± 2.4) completed a 5-minute general running warm-up before performing 3 preintervention measures of 10- to 20-m sprint. The interventions included 1, 2, and 3 sets of active dynamic stretches of the lower-body musculature (gastrocnemius, gluteals, hamstrings, quadriceps, and hip flexors) performed approximately 14 times for each exercise while walking (ADS1, ADS2, and ADS3). The active dynamic warm-ups were randomly allocated before performing a sprint-specific warm-up. Five minutes separated the end of the warm-up and the 3 postintervention measures of 10- to 20-m sprints. There were no significant time, condition, and interaction effects over the 10-m sprint time. For the 0- to 20-m sprint time, a significant main effect for the pre-post measurement (F = 10.81; p < 0.002), the dynamic stretching condition (F = 6.23; p = 0.004) and an interaction effect (F = 41.19; p = 0.0001) were observed. A significant decrease in sprint time (improvement in sprint performance) post-ADS1 (2.56%, p = 0.001) and post-ADS2 (2.61%, p = 0.001) was observed. Conversely, the results indicated a significant increase in sprint time (sprint performance impairment) post-ADS3 condition (2.58%, p = 0.001). Data indicate that performing 1-2 sets of 20 m of active dynamic stretches in a warm-up can enhance 20-m sprint performance. The results delineated that 3 sets of ADS repetitions could induce acute fatigue and impair sprint performance within 5 minutes of the warm-up.